Masalah sedimentasi dan penyelesaiannya melalui kaedah pengurusan persekitaran: satu kajian kes di Sungai Chini, Pahang - Mohd Ekhwan Toriman,; Mohd Khairul Amri Kamarudin,; Mushrifah Hj Idris,; Muhammad Barzani Gasim,; Nor Rohaizah Jamil, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
Sungai Chini is the only river that flows out of Lake Chini to Pahang River. Over the years, Sungai Chini experienced water quality detereoration due to sedimentation process and imbalance of development surrounding the catchment. The study was conducted in order to estimate the annual sediment load (tons/km2/yr), building a hydraulic model based on the capacity of the river and proposed of sediment management. Sampling survey was conducted in July 2008 until June 2009 involved three different seasons namely the normal season, wet and after raining. Three sampling stations were selected. The results showed that the estimated mean annual sediment transported out of Sungai Chini is 787,621 tons / km ² / year. Based on the statistical analysis indicates very significant correlation (R2= 0.980) between sediment load and discharge. The relationships between catchment size and sediment loads for selected streams within the lake basin also showed a significant correlation of R2 = 0824 which proved sediment production is associated with changes in land use. The study found that major sediment contributions are mainly from land use activities, the existence of weir at downstream site which trapped the sediment movement, back water flowing from Sungai Pahang and river bank erosion. This study suggests sediment control measures such as gazetting selected areas for the conservation of the lake basin, modification the structure of the weir, applying the "Monkey Cheek” in order to flushing high suspended sediment and controlling riverbank erosion